Pengaruh Penetapan Kemasan Terhadap Tingkat Loyalitas Konsumen : Studi Kasus Pada Perusahaan Pd Nanjung Bogor - Sujana, Sujana (Jurnal Ilmiah Ranggagading (JIR), 2004)
This research was conducted to compile information needed by firm to adapt to market demand, as an effort in order that being keep survive and grow in the competition environment of soft drink business that was counted high enough. By regression and correlation analysis could be know that the attribute of temulawak beverage product consumers like was at the price of 500-800 rupiah, no soda taste, and packed with inflated bottle. The factor of price affected consumers loyalty degree. Whereas the influence of taste factor and package size and shape was relatively low significant. Keywords : Cost Accounting; Package Determining; Consumersâ Loyalty.